The Influence of Political Trust on Attitude towards Public Participation in China - Manfei Cui; Yong Li (PLoS ONE, 2025)
This study aims to examine the impact of political trust on non-institutionalized public participation in China. Using comprehensive survey data from the Chinese General Social Survey (CGSS), this study presents two key research findings. First, this study finds a non-linear relationship between political trust and attitude towards non-institutionalized public participation. Generally, political trust has a negative effect on attitude towards non-institutionalized public participation. However, political trust exerts a positive impact on attitude towards non-institutionalized public participation under notably high political trust circumstances. Second, this study identifies the moderating role of social injustice experience in the relationship between political trust and the attitude towards non-institutionalized public participation. When high expectations associated with high trust are broken by a social injustice experience, this high political trust circumstance is more likely to result in dissatisfaction and positive attitude towards non-institutionalized public participation. This study contributes to deepening the understanding of the pattern of how political trust influences non-institutionalized public participation attitude in China. Valuable implications are also presented.